Infrastructure development and ape conservation - Rainer, Helga (Cambridge University Press, 2018)
Infrastructure development in Africa and Asia is expanding at breakneck speed, largely in biodiversity-rich developing nations. The trend reflects governments' efforts to promote economic growth in response to increasing populations, rising consumption rates and persistent inequalities. Large-scale infrastructure development is regularly touted as a way to meet the growing demand for energy, transport and food - and as a key to poverty alleviation. In practice, however, road networks, hydropower dams and 'development corridors' tend to have adverse effects on local populations, natural habitats and biodiversity. Such projects typically weaken the capacity of ecosystems to maintain ecological functions on which wildlife and human communities depend, particularly in the face of climate change. This title is also available as Open Access via Cambridge Core.
Title from publisher's bibliographic system (viewed on 15 Nov 2018).
Keywords: Apes -- Habitat -- Conservation -- Africa; Apes -- Habitat -- Conservation -- Asia; Infrastructure (Economics) -- Environmental aspects; Apes -- Effect of roads on